Tritium Separation and Purification Technology of Low Level Wastewater - Shikai GUO; Feng CUI; Xuejun HAN (Journal of Isotopes)
With the development of China's nuclear power and spent fuel reprocessing industries，along with the increasingly strict environmental emission standards，there is a growing demand for the safe and effective treatment and disposal of low-level tritiated wastewater generated during the operation of nuclear facilities. This article proposes a new method for tritium separation and purification of low-level tritiated wastewater using water distillation technology. An experimental system for low-level tritiated wastewater treatment was built，and a series of experiments were conducted to study the operating parameters of the system. This work conducted the first radioactive thermal trial for tritium separation and purification from the real low-level tritiated wastewater. The results show that this technology can effectively achieve efficient separation and concentration of tritium from low-level tritiated wastewater. The tritium concentration in the purified liquid was reduced to the level of 102 Bq/L，while that of the concentrated liquid reached the level of 1010 Bq/L，achieving a tritium separation factor of 9.49×107. These results demonstrate the significant potential of this water distillation technology for practical application.